Dupont Analysis of An Information Technology Enabled Competitive Advantage - Yuni Nustini (Jurnal Akuntansi dan Auditing Indonesia, 2003)
The transformation of business caused by e-business and e-commerce applications of the internet and related technologies demonstrates that information systems and information technologies are essential ingredients for business survival and success. The most often cited benefit of IT are integrating business process, increasing efficiency, sales, productivity, and competitiveness. This study is designed for determining where managers considering investment in information technology (IT) projects and users of financial statements can expect competitive advantage through an IT-enabled strategy to shown up in accounting performance measures. Thus it places a major emphasis on examining whether firms enjoying competitive advantage from IT is differ significantly from those who gain competitive advantage from other factors. Return on Assets (ROA) decomposition (DuPont Analysis) allows financial statement users to examine what is the difference between companies who gain competitive advantage shown up in accounting performance measures. From the hypothesis tested, we found that high IT-capable firms were not significantly different from their direct competitor on a number of accounting performance measure. Key words: Information technology, Competitive advantage DuPont analysis, Return on assets.